Vehicle Air Conditioner (VAC) Control System Based On Passenger Comfort: A Proof Of Concept - Suroto Munahar; Bagiyo Condro Purnomo; Muhammad Izzudin; Muji Setiyo; Madihah Mohd Saudi (IIUM Press, International Islamic University Malaysia, 2024)
Indexed by WOS/SCOPUS/ERA/MYCITE